The: Pengaruh Model Problem Based Learning Berbasis Health Literacy Terhadap Kemampuan Peserta Didik SMPN 21 Padang - Akwatul sholihati Nora fitri; Muhyiatul Fadilah; Aulia Azhar; Putri Qalbina (Al-Alam: Islamic Science Education Journal, 2026)
This research is motivated by the low critical thingking skills of students and the suboptimal application of health literacy in science learning. Learning that is still conventional causes student to be less active and unable to analyze and solve health problems independently. This study to analyze the effect of the Problem Based Learning (PBL) model based on health literacy on the critical thinking skills of eighth grade students of SMPN 21 Padang. The type of research used is quantitative with a quasi-eksperimental method and a non-equivalent control group design. The sample consisted of 32 students in each experimental and control class. The instruments used included critical thinking tests, observation sheets, and student respons questionnaires. The results showed that the PBL model based on health literacy had a significant effect on students' critical thinking skills. Observation of the implementation of the PBL model obtained a percentage of 96% with a very good category and student responses of 79% with a good category. The results of the hypothesis test using the t test obtained a value of t_count> t_table, namely 5.71> 2.00 so that was rejected and was accepted.